The Prerogative Writs as Constitutional Transfer. (7th September 2018) - Crouch, Melissa
Abstract: The courts are often a key site in the struggle for the protection and enforcement of constitutional rights and accountability. In this article, I draw attention to an important avenue for both the historical and contemporary study of comparative administrative law: the incorporation of the prerogative writs into written constitutions. I offer a global genealogy of the writs as a colonial common law transfer that took on a new life in written constitutions across former British colonies, particularly across South Asia, including India, Pakistan, Bangladesh, Sri Lanka and Myanmar, as well as parts of Africa, the Pacific and the Caribbean. I illustrate the history, development and variations of this model, transforming from the common law remedies of England to a constitutional means of protecting rights. Through the case of Myanmar, I demonstrate the history of transnational constitutional borrowing and innovation in former British colonies. The importance of the writs lies in their symbolic status as a constitutional remedy and, despite present limitations, comparative experience offers future scope for judicial activism in Myanmar.